[PP.35.24]: 24 HOUR BLOOD PRESSURE RESPONSE TO LOWER DOSE (30MG) FIMASARTAN. (June 2015) - Lee>, H.>; Kim, C.; Song, J.; Chae, S.; Jeong, M.; Kim, D.; Oh, B.
Abstract : Objective: Fimasartan is a recently developed angiotensin receptor blocker (ARB) which has comparable efficacy and tolerability with other ARBs. The objective of this study was to evaluate the 24 hour blood pressure lowering efficacy and the safety of the low dose fimasartan (30 mg once daily) compared with valsartan (80 mg once daily) in patients with mild to moderate hypertension. Design and method: We conducted phase III study using a randomized, multicenter, double-blind, parallel grouped design. After 2 weeks' placebo run-in, the eligible hypertensive patients, whose mean ambulatory blood pressure monitoring (ABPM) values were more than 135 / 85 mmHg, were randomized, and received either fimasartan 30 mg daily or valsartan 80 mg daily. The primary efficacy endpoint was the change in mean 24 hour SBP value from the baseline and at week 8. Secondary endpoints included the change in mean 24 hour DBP value from baseline and at week 8 and the trough-to-peak (T/P) ratio of each drugs. Results: Seventy five patients were randomly allocated to receive fimasartan (n = 38) or valsartan (n = 37). There was no significant difference in baseline demographic characteristics between the 2 treatment groups. At week 8, 24 hour mean SBP was significantly decreased from baseline in both groups; -10.51 [2.00] mmHg (p < 0.0001) in the fimasartan group and -6.18 [2.15] mmHg (p = 0.0307) in the valsartan group. The between group difference was 3.76 mm Hg but there was no statistical significance (p = 0.1392). The global T/P ratio of ambulatory SBP in the fimasartan 30 mg groups were 0.48 and 0.40 in the valsartan 80 mg group. The incidence of ADRs was 10.53% and 16.22% in the fimasartan and the valsartan groups, respectively. The most frequent AEs were acute pharyngitis (2 patients, 5.41%). Conclusions: In this study with eligible adult Korean patients who had mild-to-moderate hypertension, the efficacy of low dose (30 mg) fimasartan showed comparable 24 hour blood pressure lowering efficacy compared with valsartan (80 mg). There was no statistically significant difference in tolerability between the groups.